2009
DOI: 10.1111/j.1540-4781.2009.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Regulatory Strategies and Agency in Self‐Instructed Language Learning: A Situated View

Abstract: Individualized instruction, a form of materials‐centered self‐instruction, has a long, undocumented history in the United States. The context of individualized instruction requires learners to regulate their own learning processes, including their emotional responses to learning. This study offers a situated view of the processes and strategies learners use to manage the self‐instructional process. Findings of this study suggest that contextual factors such as learners' self‐beliefs and social support influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 39 publications
4
48
0
7
Order By: Relevance
“…Self-efficacy is in turn connected to the ideal L2 self, and both self-efficacy beliefs and ideal L2 self-images are the driving forces behind motivated learning behaviour, as shown in this study. Moreover, motivated learning behaviour is considered to be a crucial factor in promoting learner autonomy (Benson 2007;Ushioda 2006), while enhanced motivation is conditional upon a sense of autonomy (Bown 2009;Lamb 2001;Ushioda 2003Ushioda , 2006. As explained above, these important concepts are tightly interwoven with each other, although there are some ontological differences in the approaches researchers have taken to understanding and describing each concept and its relationships to others.…”
Section: Resultsmentioning
confidence: 99%
“…Self-efficacy is in turn connected to the ideal L2 self, and both self-efficacy beliefs and ideal L2 self-images are the driving forces behind motivated learning behaviour, as shown in this study. Moreover, motivated learning behaviour is considered to be a crucial factor in promoting learner autonomy (Benson 2007;Ushioda 2006), while enhanced motivation is conditional upon a sense of autonomy (Bown 2009;Lamb 2001;Ushioda 2003Ushioda , 2006. As explained above, these important concepts are tightly interwoven with each other, although there are some ontological differences in the approaches researchers have taken to understanding and describing each concept and its relationships to others.…”
Section: Resultsmentioning
confidence: 99%
“…For example, and Grenfell and Harris (1999) have shown how learners make decisions on what to do to facilitate learning in the context they are situated in, and Trigwell and Prosser (1991: 254) concluded that '[learning] approaches adopted by students are relational, being a function of both the student and the context'. the context they are situated in (Brown 2009;Coldron and Smith 1999;Lave 1993; van Lier 2007). This paradigm shift has had influenced studies in language learning since the 1980s (Gao 2006;Griffiths 2003;Ikeda and Takeuchi 2000;Norton and Toohey 2001;Oxford et al 2004;Politzer and McGroarty 1985).…”
Section: Introductionmentioning
confidence: 97%
“…No entanto, percebe-se que, muitas vezes, os próprios professores desses alunos não têm conhecimento teórico e prático sobre a autorregulação e variáveis a ela relacionadas como, por exemplo, a motivação, as atribuições causais, as estratégias de aprendizagem, entre outras, que exercem um papel crucial no processo de ensino e aprendizado (Berry, 2006;Martini & DelPrette, 2002, 2009Warfield, Wood, & Lehman, 2005;Woolfson & Brady, 2009;Salonen, Vauras, & Efklides, 2005). Os pesquisadores afirmam que há professores que, durante sua formação docente, não tiveram contato com essa fundamentação teórico-metodológica e que, inclusive, não foram estimulados a refletir sobre sua conduta e a aplicar as mesmas estratégias ao longo de sua trajetória acadêmica e profissional (Brunstein & Glaser, 2011;Dembo, 2001;Marini & Boruchovitch, 2014;McKeachie & Svinicki, 2006).…”
Section: Considerações Finaisunclassified
“…A coleta de dados foi realizada por meio de uma escala de inteligência verbal, um teste de conhecimento sobre o conteúdo do programa, um teste de compreensão textual e uma breve redação sobre o uso de estratégias. Os resultados revelaram que os alunos do grupo experimental se mostraram mais capazes de aplicar a estratégia cognitiva em consonância com seus objetivos, tanto durante a leitura como na recuperação das informações do texto estudado(Leutner et al, 2007) Bown (2009). buscou identificar os comportamentos autorregulatórios dos alunos durante o aprendizado de língua estrangeira (russo), realizado durante um ano letivo, por meio de um Programa de Autoinstrução.…”
unclassified